1998
DOI: 10.1128/jvi.72.9.7467-7475.1998
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Chimeras between Human (HM-175) and Simian (AGM-27) Strains of Hepatitis A Virus To Study the Molecular Basis of Virulence

Abstract: Chimeras between human (HM-175) and simian (AGM-27) strains of hepatitis A virus (HAV) were constructed to evaluate the effect of the 2C gene of AGM-27 on HAV replication in cell culture and virulence in tamarins (Saguinus mystax) and chimpanzees (Pan troglodytes). Kinetic studies and radioimmunofocus assays demonstrated that replacement of the 2C gene of HAV/7, a cell culture-adapted strain of HM-175, with that of AGM-27 drastically reduced the ability of the virus to replicate in cultured cells. Intragenic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Analysis of factors contributing to disease severity revealed no significant differences in patients' factors including age [Fujiwara et al, 1995[Fujiwara et al, , 2000], suggesting that viral factors and the individual immune responses might determine the severity. Some articles have reported that the pathogenicity of HAV could be related to cooperative mutations within 5 0 NTR and P2 protein including non-structural protein 2B and 2C, based on the study of cultured cells [Zhang et al, 1995] and simians [Raychaudhuri et al, 1998]. However, association between the clinical severity of hepatitis A and HAV genome had not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of factors contributing to disease severity revealed no significant differences in patients' factors including age [Fujiwara et al, 1995[Fujiwara et al, , 2000], suggesting that viral factors and the individual immune responses might determine the severity. Some articles have reported that the pathogenicity of HAV could be related to cooperative mutations within 5 0 NTR and P2 protein including non-structural protein 2B and 2C, based on the study of cultured cells [Zhang et al, 1995] and simians [Raychaudhuri et al, 1998]. However, association between the clinical severity of hepatitis A and HAV genome had not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive nested RT-PCR method was therefore developed to detect serum HAV RNA in the early convalescent phase of hepatitis A with high frequency [Fujiwara et al, 1997], and the viral genomes in the sera from hepatitis A patients with a variety of clinicopathological features were analyzed and the associations between certain viral regions and clinical severities were documented. It has been reported that both viral and host factors should be considered when discussing the mechanisms responsible for the severity of hepatitis A [Fujiwara et al, 2000[Fujiwara et al, , 2001[Fujiwara et al, , 2002, and that several portions of the HAV genome including the 5 0 non-translated region (5 0 NTR) and non-structural protein 2B and 2C [Fujiwara et al, 2003[Fujiwara et al, , 2007a[Fujiwara et al, ,b, 2009], whose mutations have been shown to be important for enhanced replication and virulence in cell culture systems [Zhang et al, 1995] and simians [Raychaudhuri et al, 1998], should be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of whole HAV genomes from three cases of FH and three cases of AH indicated possible associations between the severity of hepatitis A and the nucleotide substitutions in 5 0 NTR and the amino acid (aa) substitutions in 2B, although there were no unique nucleotide or aa substitutions. On the other hand, it was reported that mutations in 5 0 NTR, 2B and 2C of HAV were associated with cytopathic variants in cultured cells, and virulence in tamarins, as described above (9,10).…”
Section: Discussionmentioning
confidence: 94%
“…26 Significant differences between AGM-27 and other HAV strains, as well as its absence in humans, led to the conclusion that this strain is restricted to monkeys only. 31 Until now, data on the genetic diversity of simian HAV strains have been limited. The HAV strain of genotype V isolated in 1995 from India, contained in the vivarium of the rhesus monkey, coincided with AGM-27 by 99.8% and 100% in the nucleotide and amino acid sequence, respectively.…”
Section: Discussionmentioning
confidence: 99%